Do player à interface: escavações publicitárias no youtube em busca da relação entre os meios - Amaral Filho, Lúcio Siqueira (Universidade do Vale do Rio dos Sinos, 2016)
This research approaches the relationship between the media and their attendance in the advertising materials produced to YouTube. Therefore, a first move makes to consider the web as multimedium, since it acts as an agent of cultural and social changes in the environment which it is inserted. By establishing a dialogue with other medium, it turns out to represent them or incorporate them, appropriating their languages and grammars, in an attempt to achieve a real status, and connect users with cultural data through their computer character. In a second stage are elaborated upon the specifics of web advertising, proposing three phases in its history: a new environment, able to increase the segmentation of audiences, individualizing the heterogeneous public of the mass media; the protagonism of the medium, when its focus was the interaction with the environment itself; and the protagonism of the user, at the time building relationships from social networking sites gained strength to narrow connections between brands and consumers. After, it enters on YouTube and in the variety of approaches by authors that has it as object of study, attesting his mutant and complex character. These characteristics are observed from fragments excavated on the time of the site, leading to emerge advertising audiovisualities in the game between user and interface. Finally, through an “archaeological act” that excavated and collected advertising materials produced to YouTube through fragments founded in the time, were cartographied the constellations ambience, reform and homage, which contains empiricals of the homepage, watch page and brand channels, verticalizing the look for the identification of the relationship between the media phenomenon in these advertising materials.
Keywords: Publicidade; Arqueologia da mídia; YouTube; Audiovisualidades; Web; Advertising; Media archaeology; Audiovisualities; ACCNPQ::Ciências Sociais Aplicadas::Comunicação